Le Plan français et les études prospectives - Cazes, Bernard (L'Actualité économique, 1975)
For the last fifteen years, in France, one has seen a clear tendancy toward prospective studies that are meant for planners. Those studies may be classified into three categories: sectorial, "transversal" and general. Because of the fact that these types of works are of different nature it seems interesting to consider them separately for discussion purpose.